2012
DOI: 10.1371/journal.pone.0037431
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Dependent Efficacy of a Dual PI3K/mTOR Inhibitor, NVP-BEZ235, and an mTOR Inhibitor, RAD001, in Endometrial Carcinomas

Abstract: The PI3K (phosphatidylinositol-3-kinase)/mTOR (mammalian target of rapamycin) pathway is frequently activated in endometrial cancer through various PI3K/AKT-activating genetic alterations. We examined the antitumor effect of NVP-BEZ235—a dual PI3K/mTOR inhibitor—and RAD001—an mTOR inhibitor—in 13 endometrial cancer cell lines, all of which possess one or more alterations in PTEN, PIK3CA, and K-Ras. We also combined these compounds with a MAPK pathway inhibitor (PD98059 or UO126) in cell lines with K-Ras altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 44 publications
7
43
0
1
Order By: Relevance
“…A molecular-targeted drug may only inhibit one signaling pathway and thus, conventional chemotherapy may be required to obtain a good therapeutic effect (92). Trials of novel drugs that are able to simultaneously inhibit PI3K and mTOR have also been conducted (93,94). These include a phase I study on the use of DS-7423 for the treatment of ovarian cancer and a phase I study on the use of NVP-BEZ235 for the treatment of endometrial cancer, in which, the efficacy of NVP-BEZ235 was compared with that of everolimus (94).…”
Section: Clinical Application Of the Results From Genomic Analysismentioning
confidence: 99%
“…A molecular-targeted drug may only inhibit one signaling pathway and thus, conventional chemotherapy may be required to obtain a good therapeutic effect (92). Trials of novel drugs that are able to simultaneously inhibit PI3K and mTOR have also been conducted (93,94). These include a phase I study on the use of DS-7423 for the treatment of ovarian cancer and a phase I study on the use of NVP-BEZ235 for the treatment of endometrial cancer, in which, the efficacy of NVP-BEZ235 was compared with that of everolimus (94).…”
Section: Clinical Application Of the Results From Genomic Analysismentioning
confidence: 99%
“…rapamycin analogs). It is known that NVP-BEZ235 displays significant antitumor activities in glioblastoma, lung, breast, renal cell and uterine endometrial carcinomas (12,14,13,27).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the PI3K/Akt pathway has been observed in all subtypes of EC and associated with more aggressive disease . Furthermore, PI3K and mTOR inhibitors are in phase I/II trials in advanced EC based on molecular alterations reported in aggressive ECs (Salvesen et al 2012, Shoji et al 2012.…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%